Manfaat pemberian tepung daun kelor (Moringa oleifera) terhadap kadar IL-6 dan kolesterol LDL tikus Sprague Dawley dislipidemia - Welresna Juliatri Putri Rupiasa; Siti Fatimah-Muis; Ahmad Syauqy; Kusmiyati Tjahjono; Gemala Anjani (AcTion: Aceh Nutrition Journal, 2021)
Dyslipidemia condition causes oxidative stress that triggers inflammation. Moringa leaves are rich in fiber and antioxidants that can prevent oxidative stress and reduce inflammation. This study aimed to see, measure, and analyze the effect of Moringa flour supplementation on IL-6 and LDL levels of dyslipidemic Sprague Dawley (SD) rats. The type of study was true-experiment with randomized pre-post. Test with control. Group design. Intervention for 28 days in 4 groups of SD rats (n= 24); a consisting group of healthy rats (K-), dyslipidemic rats (K+), dyslipidemic rats respectively given 0.1g/100g BW moringa flour (P1), and 0.2 g/100g BW moringa flour (P2). ELISA and CHOD-PAP methods measured IL-6 and LDL levels. Statistical analysis used Paired t-test, One-way Anova, and Post Hoc Bonferroni. The results showed a significant decrease in IL-6 and LDL levels in the intervention group compared to the non-intervention group (p= 0,000). The reduction of IL-6 levels in the P2 group was greater than that in the P1 group but not significant. The decrease. in LDL levels in the P2 group was significantly higher than in the P1 group. It is attributed to the fiber and antioxidant content in Moringa. Fiber that can bind cholesterol and bile acids, antioxidants can regulate fat metabolism, capture free radicals and prevent oxidative stress. In conclusion, Moringa flour supplementation improved lipid profiles and inflammation compared to rats with only standard and high-fat diets